1986
DOI: 10.1002/bjs.1800730125
|View full text |Cite
|
Sign up to set email alerts
|

On-table lavage to achieve safe restorative rectal and emergency left colonic resection without covering colostomy

Abstract: On table orthograde colonic lavage has been used in a nearly consecutive series of 122 cases of restorative rectal resection (16 for acutely obstructing rectosigmoid lesions), and in a further 4 cases of acutely obstructing left colonic carcinoma, with the aim of both achieving safer anastomoses in these adverse circumstances and avoiding a covering colostomy. The technique was found to be safe and to be effective, only five temporary colostomies being required for management of anastomotic leakage. The incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(18 citation statements)
references
References 14 publications
0
16
1
1
Order By: Relevance
“…There are two options for one-stage operation: standard colectomy with on-table colonic lavage or subtotal colectomy. The safety of the colonic lavage technique has been well documented, with a mortality rate of less than 10% and an anastomotic leakage rate of 5% (79)(80)(81)(82). A prospective, randomized trial comparing subtotal colectomy with standard colectomy with colonic lavage showed that the two techniques have similar rates of complication and mortality (83).…”
Section: Obstructing Colon Carcinomasmentioning
confidence: 98%
“…There are two options for one-stage operation: standard colectomy with on-table colonic lavage or subtotal colectomy. The safety of the colonic lavage technique has been well documented, with a mortality rate of less than 10% and an anastomotic leakage rate of 5% (79)(80)(81)(82). A prospective, randomized trial comparing subtotal colectomy with standard colectomy with colonic lavage showed that the two techniques have similar rates of complication and mortality (83).…”
Section: Obstructing Colon Carcinomasmentioning
confidence: 98%
“…When curative resection of the tumor, including lymph node dissection, is performed at the initial operation, it is almost always necessary to fashion a temporary loop ileostomy or right transverse colostomy in addition to performing resection of the primary tumor and anastomosis (17)(18)(19). Primary direct anastomosis with massive intraoperative irrigation from the oral side of the tumor does not require a temporary colostomy, but such methods have the major disadvantages of a relatively long operating time and excessive invasiveness for emergency surgery in elderly patients (20)(21)(22). There have also been reports of complications such as intraoperative rupture of dilated bowel, wound infection, suture dehiscence, severe peritonitis and DIC (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Because radical resection of the cancer also includes lymph node dissection, construction of a temporary loop ileostomy or temporary loop colostomy on the right transverse colon is performed in most cases after radical resection of the primary tumor with large bowel anastomosis (24)(25)(26)(27). There are primary anastomotic procedures involving extensive intraoperative lavage from the oral side of the bowel to avoid the construction of a temporary stoma, but these procedures require a relatively long operating time and also may be excessively invasive for emergency surgery in elderly patients (28,29). Also, there have been reports of serious complications of such procedures, including intraoperative rupture of dilated bowel, DIC, wound infection and dehiscence, anastomotic leakage, and pelvic floor peritonitis (30,31).…”
Section: -------------------------------------------------mentioning
confidence: 99%